Deteksi Ekspresi Wajah Real-Time Menggunakan YOLOv12 - Rizal Adimas; Garet Al Firmansyah; Ardiansyah Ardiansyah (Universitas Muhammadiyah Klaten, 2025)
This research focuses on the development of a real-time facial expression detection system using YOLOv12. The study utilizes a secondary dataset from Kaggle, consisting of 1000 images categorized into two classes: